The Effect of Indoor Daylight Levels on Hospital Costs and Length of Stay of Patients Admitted to General Surgery - Li, Xiawei; Lou, Jianyao; Yuan, Zheping; Shi, Aiguang; Wang, Ning; Zhou, Lin; Zhao, Mingchen; Ye, Fanghe; Pan, Zikun; Wu, Yulian (Frontiers in Public Health, 2022)
Background: Indoor daylight levels can directly affect people’s physical and psychological state. However, the effect of indoor daylight levels on patient’s clinical recovery process remains controversial. To evaluate the effect of indoor daylight levels on hospital costs and average length of stay (LOS) of a large patient population in general surgery wards. Methods: Data were collected retrospectively and analysed of patients in the Second Affiliated Hospital of Zhejiang University, School of Medicine between January 2015 and August 2020. We measured light levels in the patient rooms of general surgery and assessed their association with patients’ total hospital costs and LOS. Results: A total of 2,998 patients were included in this study with 1,478 each assigned to two light level groups after matching. Overall comparison of hospital total costs and LOS among patients according to light levels did not show a significant difference. Subgroup analysis showed when exposed to higher intensity of indoor daylight, illiterate patients had lower total hospital costs and shorter LOS as compared to those exposed to lower intensity. Conclusions: Indoor daylight levels were not associated with the hospital costs and LOS of patients in the wards of general surgery, except for those who were illiterate. It might be essential to design guidelines for medical staff and healthcare facilities to enhance indoor environmental benefits of daylight for some specific population.